LEGAL OPPORTUNITIES AND CHALLENGES IN INDONESIA’S SHARIA ECONOMY POST COVID-19: A FOCUS ON DIGITALISATION AND REGULATION - Febrianty, Yenny; Vitalia, Filda; Arzuna, Pit; Ode, Haruni (Universitas Islam Negeri Mataram, 2025)
This study aims to analyse the implementation of the sharia economy in post-pandemic Indonesia by highlighting the opportunities and legal challenges faced. The main focus of this study is on aspects of legal certainty, regulatory effectiveness, and policy adaptation to the development of Islamic economic digitalisation. The study also discussed the impact of the COVID-19 pandemic on the Islamic financial sector and the halal industry as well as recovery measures that have been implemented by the government and related authorities. The method used in this study is a normative legal research method with a statutory approach (statute approach) and a conceptual approach (conceptual approach). A study was done on several Sharia economic laws, such as Law No. 21 of 2008 on Sharia banking, Law No. 33 of 2014 on Halal Product Guarantee, and fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). In addition, this study also examines the principles of Islamic economics and how they are applied in the national legal system. The results showed that although the Islamic economy experienced positive growth after the pandemic, there are still various challenges, especially in the aspects of regulatory harmonisation, legal protection for businesses and consumers, and strengthening digital infrastructure in the Islamic financial ecosystem. Sharia Fintech is one of the fastest-growing sectors, but its regulation is still in the adjustment stage to remain in accordance with Sharia principles. Sharia financial literacy is still low among the public, which is also an inhibiting factor in optimising this sector. Digitalisation and innovation of Islamic finance must be balanced with regulations that provide legal certainty and protection for all parties. In addition, increasing Islamic financial literacy is an important aspect of strengthening an inclusive and competitive Islamic economic ecosystem at the global level.